Preparation method of conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas
Through the preparation of conductive perovskite-molecular sieve composite catalyst, the problems of high energy consumption and insufficient catalyst stability of traditional VOCs treatment methods are solved, and the VOCs degradation effect with high efficiency and low energy consumption is achieved.
Patent Information
- Application Number
- CN202411739819.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
Traditional VOCs treatment methods have problems such as high energy consumption, low processing efficiency and complex equipment. Single perovskite material lacks catalytic efficiency and stability in high concentration organic waste gas treatment.
By using the preparation method of conductive perovskite-molecular sieve composite catalyst, a catalyst with high structural stability and catalytic activity is formed by compounding perovskite composed of rare earths, alkaline earths and transition metals with molecular sieves.
It realizes efficient degradation of VOCs under low temperature conditions, significantly reduces energy consumption, improves the stability and treatment efficiency of the catalyst, and is suitable for electric heated waste gas treatment systems.
Smart Images

Figure CN119524916A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite catalysts, and in particular to a method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas. Background Art
[0002] With the acceleration of industrialization, a large amount of organic waste gas, especially VOCs, is released into the atmosphere, seriously polluting the environment and posing a threat to human health. VOCs include a variety of toxic and harmful substances and are one of the main components of air pollution. Its treatment has become an important issue in the field of environmental protection. Traditional VOCs treatment methods, such as adsorption, condensation and catalytic combustion, have problems such as high energy consumption, low treatment efficiency and complex equipment. Therefore, it is urgent to develop more efficient and energy-saving treatment technologies.
[0003] In recent years, electrocatalytic purification technology has gradually become an important technical means for environmental governance due to its low operating temperature, high catalytic efficiency and energy utilization rate. Perovskite structure is widely used in electrocatalytic reactions due to its good conductivity, catalytic activity and high stability. Perovskite oxides, especially perovskite materials composed of rare earth, alkaline earth metals and transition metal elements, show excellent electrical conductivity and high temperature resistance in electrocatalytic reactions, and can effectively promote the degradation of organic waste gas at lower temperatures. However, the adsorption capacity and catalytic performance of a single perovskite material in VOCs treatment are still limited, especially when treating high-concentration organic waste gas, the catalytic efficiency and stability of the catalyst face challenges.
[0004] Molecular sieve materials have been widely used in the fields of adsorption and catalysis due to their unique porous structure and high specific surface area. Molecular sieves can provide a large number of adsorption sites, thereby effectively capturing VOCs molecules, and through synergistic effects with perovskite catalysts, improve the degradation efficiency and treatment capacity of VOCs. The combination of perovskite materials and molecular sieves can not only fully utilize the conductivity and catalytic properties of perovskite materials, but also enhance the adsorption and degradation of VOCs with the help of the high specific surface area and pore structure of molecular sieves. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and propose a method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas. The prepared composite catalyst has high structural stability, strong catalytic activity and low operating temperature, which solves many shortcomings of traditional waste gas treatment methods.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas comprises the following steps: Step S1, directly mixing a certain proportion of rare earth salt, transition metal salt, alkaline earth salt, complexing agent and a small amount of deionized water, stirring for a period of time to form a viscous slurry to obtain a mixture; Step S2, directly placing the mixture of step S1 in a muffle furnace for calcination, heating the temperature to a certain temperature at a certain heating rate, and maintaining the temperature for a period of time, so as to obtain a conductive perovskite; Step S3, ultrasonically dispersing the molecular sieve in a 70% ethanol solution, adding the conductive perovskite obtained in the above step S2, stirring for a period of time, and drying to obtain a conductive perovskite-molecular sieve composite catalyst.
[0007] Preferably, in step S1, the rare earth salt, transition metal salt and alkaline earth salt are all a mixture of one or more of nitrate, chloride, acetate and sulfate.
[0008] Preferably, in step S1, the complexing agent is citric acid, ethylenediaminetetraacetic acid, etc.
[0009] Preferably, in step S1, the rare earth salt is a metal salt of rhenium (Re), lanthanum (La), samarium (Sm), gadolinium (Gd), cerium (Ce), europium (Eu), holmium (Ho), etc.
[0010] Preferably, in step S1, the transition metal salt is a metal salt of vanadium (V), titanium (Ti), manganese (Mn), ruthenium (Ru), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), lead (Pb), zinc (Zn), cadmium (Cd), etc.
[0011] Preferably, in step S1, the alkaline earth salt is a metal salt of magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc.
[0012] Preferably, in step S1, the molar ratio of the rare earth salt or alkaline earth salt, the transition metal salt and the complexing agent is 1:1:(2-6), and the content of the injected small amount of deionized water is 5%-30% of the total mass of the mixture; the stirring time is 30-60 min, and the stirring rate is 100-1000 r / min.
[0013] Preferably, in step S2, the calcination heating rate is 1-10 °C / min; the constant temperature maintained during the calcination is 800-1000 °C, and the maintenance time of the calcination constant temperature stage is 3-12 h.
[0014] Preferably, in step S3, the molecular sieve is Y, ZSM-5 and β, and the mass of the molecular sieve is 1% to 10% of that of the perovskite.
[0015] Preferably, in step S3, the stirring time is 30-60 min, the stirring rate is 500-1000 r / min, and the drying temperature is 60-120°C.
[0016] By adopting the above technical solution: the composite catalyst is composed of a perovskite oxide formed by rare earth, alkaline earth and transition metal and a molecular sieve. The perovskite has good structural stability, conductivity and catalytic activity, and the molecular sieve provides VOCs adsorption sites for the catalyst through its large specific surface area and porous structure, promoting the efficient degradation of organic waste gas. The prepared composite catalyst has high structural stability, strong catalytic activity and low operating temperature, which solves many deficiencies in traditional waste gas treatment methods and can improve the electrocatalytic degradation efficiency of VOCs. The composite catalyst not only has good environmental adaptability, but also can play an important role in the field of electrothermal waste gas treatment, which will bring significant economic and social benefits.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. Compared with the existing single catalyst, the conductive perovskite-molecular sieve composite catalyst prepared by the present invention has a higher VOC degradation efficiency under low temperature conditions. The rich pore structure and large specific surface area provided by the molecular sieve enable VOC molecules to be adsorbed more effectively, thereby promoting the catalytic reaction at a lower temperature and significantly reducing energy consumption.
[0018] 2. The perovskite material used in the present invention is composed of rare earth, alkaline earth and transition metal, which gives the catalyst excellent structural stability and sintering resistance, and can maintain catalytic activity for a long time, avoiding the problem of catalytic performance degradation of traditional catalysts under high temperature or long-term use.
[0019] 3. Compared with traditional thermal catalysts, the composite catalyst prepared by the present invention can utilize electrical energy more efficiently, provide a more stable catalytic reaction under the synergistic effect of electricity and heat, is suitable for electric thermal exhaust gas treatment systems, and shows obvious energy-saving advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The electrothermal catalysts used in the present invention to catalyze the oxidation of benzene T 90% Performance comparison chart. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings, so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0022] Embodiment 1: (1) Take 5 mmol of lanthanum nitrate, 5 mmol of strontium nitrate, 10 mmol of cobalt nitrate, and 20 mmol of citric acid and mix them directly. Then inject 0.9 g of deionized water into the mixture and stir at 500 r / min for 30 min. (2) placing the mixture in a muffle furnace and heating it to 850°C at a heating rate of 5°C / min, and calcining at the constant temperature for 5 hours to obtain perovskite powder; (3) 1 g of the synthesized perovskite powder and 0.05 g of ZSM-5 molecular sieve powder were added to 30 mL of 70% ethanol solution, stirred at 70 °C at 600 r / min for 30 min, then the obtained solid was dried at 70 °C for 7 h, and finally calcined at 550 °C for 4 h to obtain La 0.5 Sr 0.5 CoO3 perovskite / ZSM-5 molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the electrothermal catalytic oxidation of benzene by the composite catalyst is T 90% It reached 81°C.
[0023] Embodiment 2: (1) Take 12 mmol of samarium nitrate, 12 mmol of manganese nitrate, and 18 mmol of ethylenediaminetetraacetic acid and mix them directly. Then inject 1.2 g of deionized water into the mixture and stir at 800 r / min for 45 min. (2) placing the mixture in a muffle furnace and heating it to 900°C at a heating rate of 8°C / min, and calcining at the constant temperature for 6 hours to obtain perovskite powder; (3) 1.5 g of perovskite powder and 0.015 g of Y-type molecular sieve powder were added to 40 mL of 70% ethanol solution, stirred at 700 r / min at 80°C for 40 min, then dried for 6 h, and finally calcined at 600°C for 3 h to obtain SmCoO3 perovskite / Y molecular sieve composite catalyst. 3 Benzene, 10000h -1Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the electrothermal catalytic oxidation of benzene by the catalyst is T 90% is 112°C.
[0024] Embodiment 3: (1) Take 10 mmol of rhenium nitrate and 15 mmol of citric acid and mix them directly. Inject 0.8 g of deionized water into the mixture and stir at 600 r / min for 30 min. (2) placing the mixture in a muffle furnace and heating it to 875°C at a heating rate of 6°C / min, and calcining at the constant temperature for 4 hours to obtain perovskite powder; (3) 1 g of synthesized perovskite powder and 0.1 g of β molecular sieve powder were added to 50 mL of 70% ethanol solution, stirred at 500 r / min at 60°C for 60 min, then dried at 80°C for 8 h, and finally calcined at 560°C for 4 h to obtain ReO3 perovskite / β molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the electrothermal catalytic oxidation of benzene by the composite catalyst is T 90% is 115°C.
[0025] Embodiment 4: (1) Take 8 mmol of calcium nitrate, 8 mmol of vanadium nitrate, and 25 mmol of ethylenediaminetetraacetic acid and mix them directly. Then inject 1 g of deionized water into the mixture and stir at 400 r / min for 25 min. (2) placing the mixture in a muffle furnace and heating it to 920°C at a heating rate of 7°C / min, and calcining at the constant temperature for 7 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.05 g of ZSM-5 molecular sieve powder were added to 40 mL of 70% ethanol solution, stirred at 800 r / min at 90°C for 50 min, then dried for 5 h, and finally calcined at 580°C for 3 h to obtain CaVO3 perovskite / ZSM-5 molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene 90% is 112°C.
[0026] Embodiment 5: (1) Take 10 mmol of calcium nitrate, 10 mmol of chromium nitrate, and 22 mmol of citric acid and mix them directly. Then inject 1.5 g of deionized water into the mixture and stir at 550 r / min for 35 min. (2) placing the mixture in a muffle furnace and heating it to 860°C at a heating rate of 4°C / min, and calcining at the constant temperature for 6 hours to obtain perovskite powder; (3) 1 g of synthesized perovskite powder and 0.06 g of Y molecular sieve powder were added to 50 mL of 70% ethanol solution, stirred at 700 r / min at 80°C for 40 min, then dried for 7 h, and finally calcined at 590°C for 5 h to obtain CaCrO3 perovskite / Y molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the electrothermal catalytic oxidation of benzene by the composite catalyst is T 90% is 96°C.
[0027] Embodiment 6: (1) Take 6 mmol of lanthanum nitrate, 6 mmol of strontium nitrate, 12 mmol of manganese nitrate, and 30 mmol of ethylenediaminetetraacetic acid and mix them directly. Then inject 1 g of deionized water into the mixture and stir at 600 r / min for 40 min. (2) placing the mixture in a muffle furnace and heating it to 895°C at a heating rate of 9°C / min, and calcining at the constant temperature for 8 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.07 g of β molecular sieve powder were added to 60 mL of 70% ethanol solution, stirred at 75 °C and 750 r / min for 45 min, then dried for 9 h, and finally calcined at 600 °C for 6 h to obtain La 0.5 Sr 0.5 MnO3 perovskite / β molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90% is 89°C.
[0028] Embodiment 7: (1) Take 10 mmol of strontium nitrate, 10 mmol of ferric nitrate, and 10 mmol of citric acid and mix them directly. Then inject 0.7 g of deionized water into the mixture and stir at 500 r / min for 30 min. (2) placing the mixture in a muffle furnace and heating it to 880°C at a heating rate of 5°C / min, and calcining at the constant temperature for 4 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.08 g of ZSM-5 molecular sieve powder were added to 20 mL of 70% ethanol solution, stirred at 85°C and 650 r / min for 40 min, then dried for 8 h, and finally calcined at 550°C for 5 h to obtain SrFeO3 perovskite / ZSM-5 molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90% is 120°C.
[0029] Embodiment 8: (1) Take 10 mmol of copper nitrate, 10 mmol of lanthanum nitrate, and 28 mmol of ethylenediaminetetraacetic acid and mix them directly. Then inject 1.3 g of deionized water into the mixture and stir at 600 r / min for 40 min. (2) placing the mixture in a muffle furnace and heating it to 905°C at a heating rate of 10°C / min, and calcining at the constant temperature for 9 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.09 g of Y molecular sieve powder were added to 50 mL of 70% ethanol solution, stirred at 700 r / min for 30 min at 70°C, then dried for 7 h, and finally calcined at 600°C for 6 h to obtain LaCuO3 perovskite / Y molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90 % is 134°C.
[0030] Embodiment 9: (1) Take 12 mmol titanium nitrate, 12 mmol lanthanum nitrate, and 18 mmol citric acid and mix them directly. Then inject 0.8 g deionized water into the mixture and stir at 500 r / min for 35 min. (2) placing the mixture in a muffle furnace and heating it to 895°C at a heating rate of 5°C / min, and calcining at the constant temperature for 5 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.02 g of ZSM-5 molecular sieve powder were added to 30 mL of 70% ethanol solution, stirred at 500 r / min at 60°C for 30 min, then dried for 6 h, and finally calcined at 570°C for 4 h to obtain LaTiO3 perovskite / ZSM-5 molecular sieve composite catalyst. 3 Benzene, 10000h -1Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90 % is 93°C.
[0031] Embodiment 10: (1) Take 12 mmol of strontium nitrate, 12 mmol of vanadium nitrate, and 26 mmol of citric acid and mix them directly. Then inject 1.2 g of deionized water into the mixture and stir at 700 r / min for 50 min. (2) placing the mixture in a muffle furnace and heating it to 880°C at a heating rate of 6°C / min, and calcining at the constant temperature for 8 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.04 g of Y molecular sieve powder were added to 40 mL of 70% ethanol solution, stirred at 800 r / min at 75°C for 45 min, then dried for 9 h, and finally calcined at 590°C for 5 h to obtain SrVO3 perovskite / Y molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90 % is 122°C.
[0032] Embodiment 11: (1) Take 9 mmol of strontium nitrate, 9 mmol of chromium nitrate, and 20 mmol of ethylenediaminetetraacetic acid and mix them directly. Then inject 0.9 g of deionized water into the mixture and stir at 550 r / min for 45 min. (2) placing the mixture in a muffle furnace and heating it to 900°C at a heating rate of 7°C / min, and calcining at a constant temperature for 7 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.05 g of β molecular sieve powder were added to 50 mL of 70% ethanol solution, stirred at 80 °C and 600 r / min for 40 min, then dried for 8 h, and finally calcined at 580 °C for 4 h to obtain SrCrO3 perovskite / β molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90 % is 119°C.
[0033] Embodiment 12: (1) Take 10 mmol of calcium nitrate, 10 mmol of ferric nitrate, and 22 mmol of citric acid and mix them directly. Then inject 1 g of deionized water into the mixture and stir at 450 r / min for 25 min. (2) placing the mixture in a muffle furnace and heating it to 870°C at a heating rate of 4°C / min, and calcining at the constant temperature for 6 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.06 g of Y molecular sieve powder were added to 30 mL of 70% ethanol solution, stirred at 80°C and 600 r / min for 50 min, then dried for 9 h, and finally calcined at 600°C for 5 h to obtain a CaFeO3 perovskite / Y molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene 90 % is 128°C.
[0034] Embodiment 13: (1) Take 11mmol strontium nitrate, 11mmol cobalt nitrate, and 24mmol ethylenediaminetetraacetic acid and mix them directly. Then inject 1g deionized water into the mixture and stir at 500 r / min for 30 min. (2) placing the mixture in a muffle furnace and heating it to 875°C at a heating rate of 8°C / min, and calcining at the constant temperature for 4 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.09 g of ZSM-5 molecular sieve powder were added to 30 mL of 70% ethanol solution, stirred at 70 °C and 600 r / min for 30 min, then dried for 7 h, and finally calcined at 550 °C for 4 h to obtain SrCoO3 perovskite / ZSM-5 molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene 90 % is 139°C.
[0035] Embodiment 14: (1) Take 15 mmol of lanthanum nitrate, 15 mmol of nickel nitrate, and 29 mmol of ethylenediaminetetraacetic acid and mix them directly. Then inject 0.7 g of deionized water into the mixture and stir at 500 r / min for 30 min. (2) placing the mixture in a muffle furnace and heating it to 885°C at a heating rate of 6°C / min, and calcining at the constant temperature for 6 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.1 g of β molecular sieve powder were added to 50 mL of 70% ethanol solution, stirred at 700 r / min at 85°C for 40 min, then dried for 8 h, and finally calcined at 590°C for 5 h to obtain LaNiO3 perovskite / β molecular sieve composite catalyst.3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90 % is 149°C.
[0036] Embodiment 15: (1) Take 13mmol calcium nitrate, 13mmol ruthenium nitrate, and 25mmol citric acid and mix them directly. Then inject 1g deionized water into the mixture and stir at 500 r / min for 35 min. (2) placing the mixture in a muffle furnace and heating it to 880°C at a heating rate of 5°C / min, and calcining at the constant temperature for 5 hours to obtain perovskite powder; (3) Take 1g of perovskite powder and 0.1g of β molecular sieve powder and add them to 40 mL of 70% ethanol solution, stir at 70°C and 600 r / min for 45min, then dry for 7h, and finally calcine at 580°C for 4h to obtain CaRuO3 perovskite / β molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90 % is 86°C.
[0037] Embodiment 16: (1) Take 10mmol of barium nitrate, 10mmol of lead nitrate, and 20mmol of citric acid and mix them directly. Then inject 1g of deionized water into the mixture and stir at 500 r / min for 35 min. (2) placing the mixture in a muffle furnace and heating it to 880°C at a heating rate of 5°C / min, and calcining at the constant temperature for 5 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.05 g of Y molecular sieve powder were added to 40 mL of 70% ethanol solution, stirred at 70 °C and 600 r / min for 45 min, then dried for 7 h, and finally calcined at 580 °C for 4 h to obtain BaPbO3 perovskite / Y molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90 % is 81°C.
[0038] Embodiment 17: (1) Take 5mmol of cerium nitrate, 5mmol of lanthanum nitrate, 10mmol of manganese nitrate, and 20mmol of citric acid and mix them directly. Then inject 1g of deionized water into the mixture and stir at 500 r / min for 35 min. (2) placing the mixture in a muffle furnace and heating it to 880°C at a heating rate of 5°C / min, and calcining at the constant temperature for 5 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.05 g of Y molecular sieve powder were added to 40 mL of 70% ethanol solution, stirred at 70 °C and 600 r / min for 45 min, then dried for 7 h, and finally calcined at 580 °C for 4 h to obtain La 0.5 Ce 0.5 MnO3 perovskite / Y molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene 90 % is 102°C.
[0039] Embodiment 18: (1) Take 10 mmol of europium nitrate, 10 mmol of manganese nitrate, and 20 mmol of citric acid and mix them directly. Then inject 1 g of deionized water into the mixture and stir at 500 r / min for 35 min. (2) placing the mixture in a muffle furnace and heating it to 880°C at a heating rate of 5°C / min, and calcining at the constant temperature for 5 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.05 g of ZSM-5 molecular sieve powder were added to 40 mL of 70% ethanol solution, stirred at 70 °C and 600 r / min for 50 min, then dried for 7 h, and finally calcined at 580 °C for 4 h to obtain EuMnO3 perovskite / ZSM-5 molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene 90 % is 132°C.
[0040] Embodiment 19: (1) Take 10 mmol of holmium nitrate, 10 mmol of manganese nitrate, and 20 mmol of citric acid and mix them directly. Then inject 1 g of deionized water into the mixture and stir at 500 r / min for 35 min. (2) placing the mixture in a muffle furnace and heating it to 900°C at a heating rate of 8°C / min, and calcining at the constant temperature for 6 hours to obtain perovskite powder; (3) 1 g of perovskite powder and 0.05 g of Y molecular sieve powder were added to 50 mL of 70% ethanol solution, stirred at 70 °C and 600 r / min for 50 min, then dried for 7 h, and finally calcined at 580 °C for 4 h to obtain HoMnO3 perovskite / Y molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90 % is 141°C.
[0041] Embodiment 20: (1) Take 10 mmol manganese nitrate, 1 mmol zinc nitrate, 1 mmol cadmium nitrate, 1 mmol magnesium nitrate, 7 mmol lanthanum nitrate, and 20 mmol citric acid and mix them directly. Inject 1 g of deionized water into the mixture and stir at 500 r / min for 35 min. (2) placing the mixture in a muffle furnace and heating it to 900°C at a heating rate of 8°C / min, and calcining at the constant temperature for 6 hours to obtain perovskite powder; (3) Take 1 g of perovskite powder and 0.02 g of β molecular sieve powder and add them to 50 mL of 70% ethanol solution. Stir at 70 °C and 600 r / min for 50 min, then dry for 7 h, and finally calcine at 580 °C for 4 h to obtain La 0.7 Zn 0.1 Cd 0.1 Mg 0.1 MnO3 perovskite / β molecular sieve composite catalyst. 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, the composite catalyst electrothermal catalytic oxidation of benzene T 90 % is 155°C.
[0042] Comparative Example 1: The method for preparing perovskite oxide by sol-gel method comprises the following steps: (1) Weigh 10 mmol of the nitrate of each of the above perovskite A-site elements, 10 mmol of the nitrate of the perovskite A-site element, and 30 mmol of citric acid in 100 mL of deionized water and stir at 600 r / min for 30 min; (2) heating the mixture solution in (1) to 80°C, stirring continuously to evaporate excess water to form a gel, and then drying in an oven at 120°C for 12 h; (3) The precipitate obtained in (2) is heated to 850 °C in a muffle furnace at a heating rate of 5 °C / min and maintained at this temperature for 6 h. The resulting product is the perovskite oxide catalyst.
[0043] 1 g of the perovskite oxide catalyst prepared in Comparative Example 1 was taken and heated to 1000 mg / m 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, there is no electrothermal catalytic oxidation effect below 180°C.
[0044] Comparative Example 2: Performance testing of commercial Y, ZSM-5 and β molecular sieves At 1000 mg / m 3 Benzene, 10000h -1 Under the conditions of air velocity, humidity RH=30% and voltage of 10V, 1 g of commercial Y, ZSM-5 and β molecular sieves from Control Example 2 were taken respectively, and their non-conductive ability and catalytic oxidation activity were measured.
[0045] The test performance results of the above embodiments and control examples are shown in Table 1: Table 1 shows the performance results of each instance test
[0046] In summary, the composite catalyst prepared by the present invention has high structural stability, strong catalytic activity and low operating temperature, which solves many deficiencies in traditional waste gas treatment methods and can improve the electrocatalytic degradation efficiency of VOCs. The composite catalyst not only has good environmental adaptability, but also can play an important role in the field of electrothermal waste gas treatment, which will bring significant economic and social benefits.
[0047] The description and practice disclosed in the present invention are easy to think and understand for ordinary technicians in the technical field, and several improvements and modifications can be made without departing from the principles of the present invention. Therefore, modifications or improvements made without departing from the spirit of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas, characterized in that: The following steps are involved: Step S1, directly mixing a certain proportion of rare earth salt, transition metal salt, alkaline earth salt, complexing agent and a small amount of deionized water, stirring for a period of time to form a viscous slurry to obtain a mixture; Step S2, directly placing the mixture of step S1 in a muffle furnace for calcination, heating the temperature to a certain temperature at a certain heating rate, and maintaining the temperature for a period of time, so as to obtain a conductive perovskite; Step S3, ultrasonically dispersing the molecular sieve in a 70% ethanol solution, adding the conductive perovskite obtained in the above step S2, stirring for a period of time, and drying to obtain a conductive perovskite-molecular sieve composite catalyst.
2. The method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas according to claim 1, characterized in that: In step S1, the rare earth salt, transition metal salt and alkaline earth salt are all a mixture of one or more of nitrate, chloride, acetate and sulfate.
3. The method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas according to claim 1, characterized in that: In step S1, the complexing reagent is citric acid and ethylenediaminetetraacetic acid.
4. The method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas according to claim 1, characterized in that: In step S1, the rare earth salt is a metal salt of rhenium, lanthanum, samarium, gadolinium, cerium, europium or holmium.
5. The method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas according to claim 1, characterized in that: In step S1, the transition metal salt is a metal salt of vanadium, titanium, manganese, ruthenium, iron, cobalt, nickel, copper, lead, zinc, or cadmium.
6. The method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas according to claim 1, characterized in that: In step S1, the alkaline earth salt is a metal salt of magnesium, calcium, strontium or barium.
7. The method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas according to claim 1, characterized in that: In step S1, the molar ratio of the rare earth salt or alkaline earth salt, the transition metal salt and the complexing agent is 1:1:(2-6), and the content of the injected small amount of deionized water is 5%-30% of the total mass of the mixture; the stirring time is 30-60 min, and the stirring rate is 100-1000 r / min.
8. The method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas according to claim 1, characterized in that: In step S2, the calcination heating rate is 1-10 °C / min; the constant temperature maintained during the calcination is 800-1000 °C, and the maintenance time of the calcination constant temperature stage is 3-12 h.
9. The method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas according to claim 1, characterized in that: In step S3, the molecular sieves are Y, ZSM-5 and β, and the mass of the molecular sieve is 1% to 10% of the perovskite.
10. The method for preparing a conductive perovskite-molecular sieve composite catalyst for electrocatalytic purification of organic waste gas according to claim 1, characterized in that: In step S3, the stirring time is 30-60 min, the stirring rate is 500-1000 r / min, and the drying temperature is 60-120°C.